2005
DOI: 10.1111/j.1348-0421.2005.tb03656.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Vaccination with Toxoplasma Lysate Antigen and CpG as an Adjuvant against Toxoplasma gondii in Susceptible C57BL/6 Mice

Abstract: Infection with the intracellular protozoan parasite Toxoplasma gondii causes serious public health problems to both humans and livestock and of great economic impact worldwide. Oligodeoxynucleotides (ODN) which contain immunostimulatory CG motifs (CpG ODN) can promote Th1 responses, an adjuvant activity that is desirable for vaccination against intracellular pathogens. We investigated the feasibility of using CpG as an adjuvant combined with Toxoplasma lysate antigen (TLA) as a vaccine against toxoplasmosis. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…El‐Malky et al. (28) and Kringel et al. (40) reported CpG ODN to be an effective adjuvant for use in vaccination against toxoplasmosis in mice and pigs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…El‐Malky et al. (28) and Kringel et al. (40) reported CpG ODN to be an effective adjuvant for use in vaccination against toxoplasmosis in mice and pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, the role of CpG ODN as an adjuvant in vaccination against T. gondii infection has been debatable. El-Malky et al (28) and Kringel et al (40) reported CpG ODN to be an effective adjuvant for use in vaccination against toxoplasmosis in mice and pigs. However, Saavedra et al (41) found that CpG ODN had only a limited role in the protection against T. gondii in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with either low 1 × 10 2 or high (1 × 10 3 or 1 × 10 5 ) doses of viable RH (25). Total tachyzoite lysate antigen was prepared from in vitro HFF cultures of RH as described (26, 27). For cytokine assays mice were infected i.p.…”
Section: Methodsmentioning
confidence: 99%